Molecules, morphology and minute hooded beetles: a phylogenetic study with implications for the evolution and classification of Corylophidae (Coleoptera: Cucujoidea). (3rd October 2012) - ROBERTSON, JAMES A.; ŚLIPIŃSKI, ADAM; HIATT, KEVIN; MILLER, KELLY B.; WHITING, MICHAEL F.; MCHUGH, JOSEPH V.
<x xml:space="preserve">Abstract</x> Eight genes (nuclear: 18S, 28S, H3, CAD; mitochondrial: 12S, 16S, COI, COII) and morphology were used to infer the evolutionary history of Corylophidae, some of the smallest free‐living insects. The study included 36 corylophid exemplars, representing approximately 60% of the known generic diversity of the family and 16 cucujoid outgroup taxa. Multiple partitioning strategies, molecular datasets, combined datasets and different taxon sampling regimes using maximum likelihood and mixed‐model Bayesian inference were utilized to analyse these data. Most results were highly concordant across analyses. There was strong agreement across (i) partitioning strategies, (ii) maximum likelihood and Bayesian inference analyses of the molecular data, and (iii) Bayesian inference of the molecular data alone and Bayesian inference of the combined morphological and molecular data when all terminal taxa were included. When a strict taxon sampling protocol was employed so that only single generic exemplars were included, deep relationships were affected in the resulting phylogenetic hypotheses. Under such narrow sampling strategies, deep phylogenetic relationships were also sensitive to the choice of generic exemplars. Although it is often challenging to obtain single representatives for many taxa in higher‐level phylogenetic analyses, these results indicate the importance of using denser taxon sampling approaches even at the specific level for genera included in such studies. Molecular data alone support Anamorphinae (Endomychidae) strongly as the sister group of Corylophidae. In combined data analyses, Coccinellidae is recovered as the sister group to Corylophidae. In all analyses, Corylophidae and the subfamily Corylophinae are recovered as monophyletic. The monophyly of Periptyctinae was untested, as only a single species was included. All included corylophine tribes were recovered as monophyletic with the exception of Aenigmaticini; Aenigmaticum Matthews forms the sister group to Orthoperus Stephens and StanusŚlipiński et al. is recovered as the sister group of Sericoderus Stephens. Stanus tasmanicusŚlipiński et al. is transferred to a new genus, Pseudostanus Robertson, Ślipiński & McHugh gen.n.incertae sedis. We propose a new tribe, Stanini Robertson, Ślipiński & McHugh trib.n. for Stanus bowesteadiŚlipiński et al. and a new concept of Aenigmaticini sensu.n. to include only the nominate genus. Anatomical transitions associated with corylophid miniaturization are highlighted. Key phenotypic modifications and elevated rates of substitution in nuclear rRNA genes are evident in a subgroup of Corylophinae that includes the most diminutive species. Other taxonomic and evolutionary implications are discussed in light of the results.